HUBUNGAN AUDIT PAJAK TERHADAP KINERJA MASYARAKAT DALAM PEMBAYARAN PAJAK KENDARAAN RODA 2 (Studi Kasus Pada Kantor SAMSAT Kota Bengkulu) - Weni Susanti; Subaeti Subaeti; Rendi Rendi (LPPM Universitas Bina Insan, 2020)
This study aims to determine the results of the tax audit, determine the performance of the community in paying tax for motorcycle, and determine the relationship of tax audits on community performance in paying tax for motorcycle at SAMSAT Office in Bengkulu. Data analysis method uses product moment correlation. The results of the tax audit calculation at SAMSAT Bengkulu Office have an average value of 4.063, it mean that the tax audit at SAMSAT Office in Bengkulu is already good or high. Then the results of the calculation of public performance in the payment tax for motorcycle have an average value of 4.00, it mean that the performance of the community in paying tax for motorcycle is also good or has a high performance. The result of product moment correlation analysis states that the tax audit is related to the performance of the community in paying tax for motorcycle, with a t-test value greater than 20.60 than the t-table value (1.99). This result means thatHo being rejected and Ha being accepted, it mean that the tax audit is significantly related to the performance of the community in paying the tax for motorcycle.